2016
DOI: 10.1080/02533839.2016.1191376
|View full text |Cite
|
Sign up to set email alerts
|

An application of blended fly ash and residual rice husk ash for producing green building bricks

Abstract: The present study investigates the possibility of using a blended class-F fly ash (FA) and residual rice husk ash (RHA) in the production of green building bricks through the application of densified mixture design algorithm (DMDA) in order to provide a new use for solid waste materials. This study uses unground rice husk ash (URHA) as a partial fine aggregate substitution (10-40%) in the studied cementitious mixtures. Solid bricks of 220 × 105 × 60 mm in size were prepared under forming pressure of 25-35 MPa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Unfired building bricks were prepared in a steel mold, with dimensions of 220×105×65 mm, applying forming pressure of around 5 MPa that is much lower than the forming pressures used in most of the previous studies (10-35 MPa) [3][4][5][6][11][12][13][14][15][16]. The purpose of this study is to assess the use of low forming pressure and industrial and agricultural by-products for producing unfired building bricks.…”
Section: Samples Preparation and Test Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfired building bricks were prepared in a steel mold, with dimensions of 220×105×65 mm, applying forming pressure of around 5 MPa that is much lower than the forming pressures used in most of the previous studies (10-35 MPa) [3][4][5][6][11][12][13][14][15][16]. The purpose of this study is to assess the use of low forming pressure and industrial and agricultural by-products for producing unfired building bricks.…”
Section: Samples Preparation and Test Programsmentioning
confidence: 99%
“…Recently, rice husk ash has been used for producing unfired building bricks [12][13][14][15][16]. Unfired building bricks were made from FA, rice husk ash, and sand using geopolymerization technology [12][13][14]. Other unfired building bricks were made from cement, FA, and rice husk ash based on the cementing reaction [15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Re-utilization of these kinds of wastes as usable construction materials is an effective approach and also further brings economic benefits. In Vietnam, for instance, several studies have carried out to investigate the application of various industrial wastes such as unground rice husk ash [7], fly ash and residual rice husk ash [8], ground granulated blastfurnace slag, and circulating fluidized bed combustion ash [9] as construction materials. However, the use of waste bottom ash from incineration plants (IBA) as source material for producing construction materials has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies investigated the use of rice husk as a component in fired -clay bricks [18][19][20][21], others used rice husk ash in the production of unburnt bricks [1,22]. It is noticed that ground rice husk ash can be used as binder materials [1,[22][23][24], whereas unground rice husk ash can be used as fine aggregate [1,22]. Most of test results indicated that both the unit weight and compressive strength of bricks reduced, but the water absorption of bricks increased with the increase in rice husk content.…”
Section: Introductionmentioning
confidence: 99%